2015
DOI: 10.1007/s10853-015-9135-5
|View full text |Cite
|
Sign up to set email alerts
|

Red-to-black electrochromism of 4,9-dihydro-s-indaceno[1,2-b:5,6-b’]dithiophene-embedded conjugated polymers

Abstract: A series of 4,9-dihydro-s-indaceno[1,2-b:5,6-b 0 ]dithiophene-based conjugated polymers with 3,4-bis (dodecyloxy)thiophene, 3,3-bis((dodecyloxy)methyl)-3,4-dihydro-2H-thieno [3,4-b] [1, 4] dioxepine and 3,4-ethylenedioxythiophene as co-monomers were synthesized via Stille coupling reaction in more than 50 % yields. These polymers possess relatively high number-average molecular weights of 14,900-21,000 g mol -1 and exhibit good solubility in common organic solvents. The physical and electrochemical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…An alternative strategy for accessing high-gap ECPs involved utilizing acyclic dioxythiophene polymers (PAcDOTs) that were functionalized with branched alkoxy solubilizing chains and copolymerized with 3,4-dimethoxythiophene or ethylenedioxythiophene. The PAcDOT-based polymers represented a new class of orange and red ECPs that exhibit λ max values between 485 and 525 nm while maintaining relatively low onsets of oxidation due to the electron-donating nature of the oxygen atom adjacent to the thiophene backbone. This work was advantageous beyond the seminal work on red electrochromics based on substituted thiophenes and has since motivated other research groups to realize diverse strategies to access conjugated polymers in the same color space, culminating in red ECPs being synthesized with benzotriazole, phenanthrocarbazole, indacenodithiophene, , and thienothiophene building blocks. However, these systems suffer from poor electrochromic contrast or exhibit colored-to-colored electrochromic properties and are not suited for transmissive electrochromic applications.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative strategy for accessing high-gap ECPs involved utilizing acyclic dioxythiophene polymers (PAcDOTs) that were functionalized with branched alkoxy solubilizing chains and copolymerized with 3,4-dimethoxythiophene or ethylenedioxythiophene. The PAcDOT-based polymers represented a new class of orange and red ECPs that exhibit λ max values between 485 and 525 nm while maintaining relatively low onsets of oxidation due to the electron-donating nature of the oxygen atom adjacent to the thiophene backbone. This work was advantageous beyond the seminal work on red electrochromics based on substituted thiophenes and has since motivated other research groups to realize diverse strategies to access conjugated polymers in the same color space, culminating in red ECPs being synthesized with benzotriazole, phenanthrocarbazole, indacenodithiophene, , and thienothiophene building blocks. However, these systems suffer from poor electrochromic contrast or exhibit colored-to-colored electrochromic properties and are not suited for transmissive electrochromic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, thiophene-based ECPs with red neutral state were electrochemically prepared when researchers attempted to optimize the polymerization methods and performance of the polymers. Afterward, Reynolds’ group started to develop red ECPs and prepared some processable polymers composed of 3,4-propylene­dioxythiophene (ProDOT) or alkoxy-substituted thiophenes, but these polymers retained unavoidable hues of magenta or pink color. On the basis of these pioneering work, Xu’s group recently developed a series of processable decent red-to-transmissive copolymers by oxidative polymerization, which exhibited saturated neutral color, high contrast, and fast switching. , Aiming to improve further the performance of ECPs, new building blocks such as benzotriazole, phenanthrocarbazole, and 4,9-dihydro- s -indaceno­[1,2- b :5,6- b ]­dithiophene (IDT) were introduced and copolymerized with conventional thiophene derivatives. Despite great efforts, it is still difficult to combine the desirable color with high performance, inspiring us to consider unconventional moieties to search novel solution-processable red electrochromic polymers with promising performance.…”
Section: Introductionmentioning
confidence: 99%
“…From AFM study, porous structures have been observed, which could facilitate solvent/electrolyte diffusion. , Moreover, the lower roughness of PEBE-PBP might imply a more compact surface morphology, which could be induced by the different distribution of modified moieties with side chains. With lower roughness, the diffusion of moisture and oxygen would be reduced into the interior of the polymer film, which might result in better stability of PEBE-PBP than PEB-P during both p-doping and n-doping tests. It is worth mentioning that the surface morphology would critically influence the electrochemical performances of electroactive polymers, , but a clear and exact mechanism has not been fully understood for our recombined polymers yet.…”
Section: Resultsmentioning
confidence: 99%